Profiling of User Satisfaction Level toward Ciputra Information System (CIS) - Basauli Tambunan, Damelina; Siebert, Steve (KnE Social Sciences, 2020)
This study aims to determine the average level of user satisfaction toward an information system named Ciputra Information System (CIS) which used by Universitas Ciputra on daily basis. There five dimensions used in this study to measure the satisfaction level of users toward CIS; which is Competence of e-Service Support Staff, System availability, Service Portfolio, Responsiveness, and Reliability. The analytical tool used in this study is descriptive statistics and supported by phenomenology. The population in this study are clustered in three group; they are students, lecturers, and operational staffs. The cluster sampling method are used for the clustered population to obtain the statistics data through the questionnaire. The level of satisfaction for each sample group is 3.99 for students, 3,705 for lecturers, and 3,838 for non-lecturer staff with an overall average score of 3,844. There are only two factors that get an average above 4,0; namely Competence of e-Service Support Staff and System availability. Keywords: Satisfaction Level; Information System (IS); IS Performance